'Social' value creation as care: the perspective of beneficiaries in social entrepreneurship. Issue 3 (7th July 2020) - Lorenzo-Afable, Diana; Lips-Wiersma, Marjolein; Singh, Smita
Abstract : Purpose: This paper aims to characterise the "social" in social entrepreneurship (SE) by examining social value creation (SVC) from the perspective of vulnerable beneficiaries within a developing country context. It uses the lens of care ethics to garner insights into SVC based on what beneficiaries care about in their work engagement with social enterprises. Design/methodology/approach: The exploratory paper implements a multiple case study approach to theory building, which considers the rich, real-life developing country context wherein much SVC occurs. Data collection primarily uses in-depth interviews with beneficiaries in accordance with socially sensitive research methodologies involving vulnerable participants. Findings: The findings offer an ethical view of SVC that is premised on what is of value to beneficiaries in SE. The authors find that SVC is a multi-dimensional and reciprocal process that is shaped as beneficiaries work for social enterprises. The reciprocal nature of the process engenders beneficiary altruism, which may heighten vulnerability and lead to the dark side of SE. Social implications: Many of the problems SE tries to address are situated in developing countries. The findings may enable social entrepreneurs, policymakers and social enterprise organisations to develop more responsive and more impactful solutions to social problems in developing countries. They further suggest that beneficiaries must not be looked upon merely as passive recipients of value but as active participants in the SVC process. Originality/value: This paper contributes to critical SE discourse by giving voice to beneficiaries in SE.